Survival of the greenest: environmental sustainability and longevity of organizations - Daria M. Haner; Yilei Wang; Deniz S. Ones; Stephan Dilchert; Yagizhan Yazar; Karn Kaura (Frontiers in Organizational Psychology)
Much research has been devoted to how environmental sustainability of organizations is related to organizational reputation and financial performance, but little is known about whether and how organizational environmental sustainability relates to longevity of organizations. We quantitatively examined the relation between organizational longevity and environmental sustainability of organizations, hypothesizing a positive relationship. Using two large samples of organizations—one from the U.S., and another from multiple regions (Europe, the Middle East and North Africa, and Asia, analyzed separately)—results indicate a significant, replicable positive relation between organizational longevity and environmental sustainability performance. Statistically controlling for organizational wealth and size of workforces did not appreciably diminish relations. Additionally, older organizations demonstrated better resource use and management, operational eco-efficiency, climate strategy, and environmental reporting. However, differences in innovation were less pronounced, though still favored older organizations. We discuss the implications for human resources and evolutionary theories of organizations, suggesting it is not the largest companies that endure, nor the wealthiest, but those most committed to environmental sustainability.